Induced rearrangement of kappa genes in the BLIN-1 human pre-B cell line correlates with germline J-C kappa and V kappa transcription (The Rockefeller University Press, 1991)
The human pre-B acute lymphoblastic leukemia cell line, BLIN-1, has been previously shown to undergo kappa light chain rearrangement in vitro, making it a valuable resource for analyzing pre-B to B cell differentiation. We have examined the recombination potential of BLIN-1 by characterizing several independently derived kappa-expressing subclones for DNA rearrangement and V kappa gene usage. Analysis of five kappa-expressing subclones (all having the same heavy chain rearrangement) demonstrated independent kappa light chain rearrangement events by DNA hybridization analysis. Northern blot analysis using probes recognizing the four different V kappa families revealed that two subclones used the most proximal V kappa (V kappa IV), one subclone used a V kappa I, and one subclone used a V kappa II. By polymerase chain reaction analyses, we detected transcripts from rearranged V-J-C kappa genes as well as transcripts from germline J-C kappa and V kappa in BLIN-1 cells induced to rearrange the kappa locus. kappa germline transcripts were also detected in normal developing B cell populations in fetal liver and bone marrow. Our collective results indicate that: (a) BLIN-1 can be induced to rearrange the kappa locus, and this correlates with the expression of germline kappa locus transcripts that may play a role in activating or targeting gene rearrangement; and (b) active rearrangement and usage of V genes representing different kappa families suggest that, like in the mouse, repertoire diversification in humans occurs in the presence of a fixed heavy chain rearrangement.